On the Literature and Thought of the German Classical Era : Collected Essays. - Nisbet, Hugh Barr. (Open Book Publishers, 2021)
This elegant collection of essays ranges across eighteenth and nineteenth-century thought, covering philosophy, science, literature and religion in the 'Age of Goethe.' A recognised authority in the field, Nisbet grapples with the major voices of the Enlightenment and gives pride of place to the figures of Lessing, Herder, Goethe and Schiller.